2021
DOI: 10.3390/pharmaceutics13091415
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Effectively Promoted Cell Death in Bladder Cancer and the Improved Intravesical Adhesion Drugs Delivery Strategy Could Be Better Used for Treatment

Abstract: Cannabidiol (CBD), a primary bioactive phytocannabinoid extracted from hemp, is reported to possess potent anti-tumorigenic activity in multiple cancers. However, the effects of CBD on bladder cancer (BC) and the underlying molecular mechanisms are rarely reported. Here, several experiments proved that CBD promoted BC cells (T24, 5637, and UM-UC-3) death. For example, T24 cells were treated with 12 µM CBD for 48 h, flow cytometry analysis demonstrated that early and late apoptotic cells were accounted for by 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…In bladder cancer, the effects of cannabis or compounds isolated from cannabis have not been extensively studied. A study recently demonstrated that the combination of Δ 9 -tetrahydrocannabinol and cannabichromene produced synergistic effects in a bladder cancer model (Anis et al 2021), while another focused on the effects of cannabidiol and their potential formulation within nanoparticles to treat bladder cancer (Chen et al 2021). Here, we show that other compounds from cannabis, like cannflavin A, may also induce beneficial cytotoxic and synergistic effects on bladder cancer cells.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In bladder cancer, the effects of cannabis or compounds isolated from cannabis have not been extensively studied. A study recently demonstrated that the combination of Δ 9 -tetrahydrocannabinol and cannabichromene produced synergistic effects in a bladder cancer model (Anis et al 2021), while another focused on the effects of cannabidiol and their potential formulation within nanoparticles to treat bladder cancer (Chen et al 2021). Here, we show that other compounds from cannabis, like cannflavin A, may also induce beneficial cytotoxic and synergistic effects on bladder cancer cells.…”
Section: Discussionmentioning
confidence: 57%
“…Our results showed that while some synergy is possible with gemcitabine or cisplatin, much higher levels of synergy occurred when cannabinoids like Δ 9tetrahydrocannabinol, cannabichromene, or cannabivarin are combined with cannflavin A. In recent years, several groups have begun exploring the potential of cannabinoids as anticancer agents, and this in various cancer types (Blasco-Benito et al 2018;López-Valero et al 2018a, b), including bladder cancer (Anis et al 2021;Chen et al 2021).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“… 79 The studies highlight the fact that delivery of phytochemicals with nanostructures is of importance in increasing their capacity for cell death induction and this is favorable for bladder cancer therapy (Figure 1 ). 80 , 81 , 82 However, more studies regarding molecular pathways affected by phytochemical‐loaded nanostructures, their internalization route, and development of smart and other kinds of nanoparticles are vital. The advantages related to nanostructures are the evaluation of particle size, zeta potential, and encapsulation efficiency after the loading of chemotherapeutic agent.…”
Section: Nanoplatforms In Chemotherapeutic Drug Deliverymentioning
confidence: 99%
“…Survivin Might Mediate Tumor Cell's MDR via the PI3K/Akt/mTOR Pathway PI3K/Akt/mTOR signaling pathway was necessary for tumor cells' survival (Khan et al, 2013;Riquelme et al, 2016;Chen et al, 2018;Liu et al, 2020;Chen et al, 2021) (e.g., breast cancer (Yin et al, 2017;Nunnery and Mayer, 2020), head and neck cancer (Marquard and Jücker, 2020), and lung cancer (Tan, 2020)). This pathway also played an essential role in promoting cell growth, proliferation, metastasis, and chemotherapy resistance (Khan et al, 2013;Ahmad et al, 2020;Liu et al, 2020).…”
Section: The Synergistic Of Survivin With P-gp Might Mediate Mdrmentioning
confidence: 99%